The Effectiveness Of Animation Video In Teaching Speaking To Junior High School - Kurniati, Kurniati (LPPM Universitas Mercu Buana Yogyakarta, 2016)
AbstractThere were many problems happened in the E n g l i s h l e a r n i n g p r o c e s s i n S M P N 1 S e ye g a n , s u c h a s ; (1) the students were afraid of expressing their ideas; (2) they were lack of vocabularies; (3) they were bored in studying English including in their learning speaking. Thus, this research was intended to find out the effectiveness of animation video in teaching speaking to seventh graders in SMP N 1 Seyegan-Sleman. It involved 32 students of 7A as experimental class and 7B as control class. It was experimental study to overcome students’ problem in learning English speaking skill and used pre-test and post-test as the instrument. The used design was quasi-experimental study. It was done with pre-test before treatments and post-test after having treatments. It was found that teaching speaking using animation video was effective. It can be seen from the result of the statistical computation using t- test. The t-test result of post-test in both of classes was 2.170 while t-table with the degree of freedom N-2 at 5% significance level was 1.999. It means that the result of the t-test was higher than ttable. Therefore, teaching speaking skill using animation video was considered effective. Based on this finding the researcher suggested to the teachers to use animation video in improving speaking skill especially for students in Junior High Schools.